ManipAnalysis - a software application for the analysis of force field experiments - Stockinger, C.; Pöschl, M.; Focke, A.; Stein, T. (International Journal of Computer Science in Sport, 2012)
Force field experiments are a common tool for research on internal models which are an issue of great interest in human movement science. In this paper we introduce the software ManipAnalysis which was developed for the analysis of such force field experiments. Thereby, we extracted common requirement specifications from recent studies and our own practical experience. Only depending on .NET framework, SQL-database, and MATLAB, ManipAnalysis offers a hand-in-hand solution ranging from data import and storage, up to visualization and export possibilities of calculated adaptation parameter values. Hence, ManipAnalysis fills the gap between data acquisition with the help of a robotic device and statistical analysis with statistics software applications.